Systematics, distribution, and conservation status of Dice's cottontail, Sylvilagus dicei Harris, 1932 (Mammalia, Lagomorpha, Leporidae), in Central America. Issue 1 (23rd October 2020) - Mora, José M.; Silva, Sofia M.; López, Lucía I.; Burnham–curtis, Mary K.; Wostenberg, Darren J.; French, Johnnie H.; Ruedas, Luis A.
Abstract : Dice's cottontail, Sylvilagus dicei, only was recognized as a valid species in 1981 after having been subsumed in synonymy with S . brasiliensis and S . gabbi, which latter also at times had been synonymized with an ill-defined and broadly distributed S . brasiliensis . Phylogenetic relationships of S . dicei remain poorly resolved, as does the distribution of the species. We collected new specimens of S . dicei and carried out phylogenetic analyses of combined cytochrome- b and 12S rRNA mitochondrial loci. Molecular data confirm the taxonomic status of S . dicei as a species and place it basal to the South American S . brasiliensis radiation; the successive sister taxon to this clade is Gabb's cottontail, S . gabbi . Time-calibrated analyses support simultaneous internal diversification events in S . dicei and S . gabbi ∼250 KYA. The new specimens, together with literature and museum records including the holotype, enabled us to more accurately map the distribution of S . dicei . Specimens are restricted to forested uplands in Costa Rica and western Panama. Although the total altitudinally suitable area for the species is 10, 313 km 2, removal of urban and agricultural areas not suited for its habitation result in a fragmented range of 9, 115 km 2 . Conservation threats include high predation loads from the invasive coyote, Canis latrans, urbanization, agriculture, and hunting.